Cancers in Australia in 2010 attributable to modifiable factors: summary and conclusions - David C. Whiteman; Penelope M. Webb; Adele C. Green; Rachel E. Neale; Lin Fritschi; Christopher J. Bain; D. Max Parkin; Louise F. Wilson; Catherine M. Olsen; Christina M. Nagle; Nirmala Pandeya; Susan J. Jordan; et al. (Elsevier, 2015)
Abstract Objective: To estimate the numbers and proportions of cancers occurring in Australia in 2010 attributable to modifiable causal factors. Methods: We estimated the population attributable fraction (PAF) of cancers associated with exposure to 13 causal factors using standard formulae incorporating exposure prevalence and relative risk data. We also calculated the potential impact of changing exposure to some factors. Results: A total of 32% of all cancers diagnosed in Australia in 2010 (excluding keratinocyte cancers) were attributable to the 13 factors assessed (men 33%; women 31%). Leading factors were tobacco smoke (PAF all cancers: 13.4%), solar radiation (6.2%), inadequate diet (6.1%) and overweight/obesity (3.4%). Factors conferring highest PAFs differed by sex: highest PAFs for men were tobacco smoke (15.8%), solar radiation (7.1%) and alcohol (3.0%); while highest PAFs for women were tobacco smoke (10.1%), solar radiation (5.0%) and overweight/obesity (4.5%). Sites with the highest counts of potentially preventable cancers were lung (8,569), colorectal (7,404), melanoma of the skin (7,220) and breast (3,233). Conclusions: At least one in three cancers in Australia is attributable to exposure to known modifiable factors. Implications: Up to 37,000 cancers could be prevented in Australia each year if the population avoided exposure to 13 common factors known or strongly suspected to cause cancer.